Drought-vulnerable vegetation increases exposure of disadvantaged populations to heatwaves under global warming: A case study from Los Angeles. (June 2023) - Dong, Chunyu; Yan, Yu; Guo, Jie; Lin, Kairong; Chen, Xiaohong; Okin, Gregory S.; Gillespie, Thomas W.; Dialesandro, Jake; MacDonald, Glen M.
Highlights: We examined the unequal drought impact on urban vegetation in Los Angeles. Neighborhoods of disadvantaged groups had severer vegetation degradation in drought. Decreased vegetation greenness induced higher heat exposure of Hispanics and Blacks. Urban vegetation's cooling effect in drought is linked to socioeconomic conditions. Abstract: Urban vegetation is valuable in alleviating local heatwaves. However, drought may decrease vegetation health and limit this cooling effect. Here we use satellite-based Normalized Difference Vegetation Index (NDVI) and Palmer Drought Severity Index (PDSI) to investigate the sensitivity of urban vegetation to drought in Coastal Greater Los Angeles (CGLA) from 2001 to 2020. We applied four statistical models to analyze the relations between 15 socioeconomic variables and the vegetation's sensitivity to drought. We then examined the changes in the cooling effect of the urban vegetation during drought and non-drought periods using remotely sensed land surface temperature (LST) data. The results suggest that economically disadvantaged areas with higher proportions of Hispanics and Blacks are typified by vegetation more sensitive to drought, which is likely linked to inequality in water use. Moreover, these populations experience a lower degree of vegetation cooling effects and higher exposure to heatwaves. The findings of this study imply that the potential of a community's vegetation in mitigating heatwaves is significantly influenced by the socioeconomic conditions of the community. Increasing the resilience of urban vegetation to drought in disadvantaged communities may help promote environmentally sustainable and socially resilient cities under a warming climate.